Waste black tea leaves (Camelia sinensis) as a sustainable source of tannin natural colorant for bio-treated silk dyeing - ÖZOMAY, MERAL (Springer Science and Business Media Deutschland GmbH, 2021)
Abstract : Environmentally friendly products are the need of the hour, particularly in this pandemic situation because synthetic products need such toxic chemicals for their formulation and finishing which are carcinogenic for the globe. The current study is the utilization of waste black tea leaf (BT)–based tannin brown natural colorant for silk dyeing using microwave treatment. Dye (tannin) has been isolated in various media before and after microwave treatment up to 6 min and applied at various conditions. It has been found that 30 mL of aqueous extract of 3.0 pH obtained from 6.0 g of powder containing 3.0 g/100 mL of salt as an exhausting agent after microwave treatment for 5 min, when employed at 55 °C for 45 min, has given good color yield onto silk. Iron (3%) and acacia extract (2%) as pre-chemical and bio mordant, iron (2%) and pomegranate extract (2%) as post chemical and bio-mordant, and Al (3 %) and pomegranate extract (3%) as meta chemical and bio-mordant have given new shades with good to excellent fastness ratings. It is inferred that waste black tea leaves (BTs) in an aqueous medium have an excellent potential to serve as a source of natural tannin brown dye for the coloration of surface-modified silk fabrics under the influence of cost, energy, and time-effective microwave treatment. Additionally, the utilization of a low amount of sustainable chemical and bio-mordants has valorized the dyeing of silk by developing soothing and sustainable shades with good fastness properties. Graphical abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Bio-mordants; Camelia sinensis; Microwave; Silk fabric; Sustainability; Tannin